Examining the impact of relationship-related and process-related factors on project success: the paradigm of Stimulus-Organism-Response. Issue 1 (2nd January 2022) - Li, Xiaolin; Yin, Yilin; Zhang, Ruirui
ABSTRACT: Adopting the Stimulus-Organism-Response paradigm, this paper investigates how relationship-related factors (asymmetric dependence and trust) and process-related factors (communication and coordination) influence project success. Data gathered from 173 respondents with electronic questionnaire were analyzed by Smart-PLS 3.0 software and PROCESS. The results demonstrate that project success is influenced by the relationship-related factors (asymmetric dependence and trust) between partners. Project-related factors, namely communication and coordination make the mechanism of project success more complicated. Moreover, the configuration of project control rights does not moderate the relationships among the relationship-related factors, process-related factors and project success. These findings contribute to the literature by showing the factors leading to project success and extend the literature in the domain of construction project management by presenting a Stimulus-Organism-Response paradigm and multiple serial meditations. Graphical Abstract: uf0001